Assessment of Piper betle L. Methanolic extract as a potential growth and health promoter for juvenile red hybrid tilapia (Oreochromis sp.) - Ahmad, Syahidah (2018)
Tilapia is listed as the most widely cultured fish in many parts of the world. The rising global demand of tilapia has driven significant efforts for the improvement of the growth and health of this species. Various antibiotics, growth promoters, and chemotherapeutic agents have been used for the above purposes. However, they tend to bring undesirable side effects. The use of herbs has been suggested as an alternative strategy to the use of conventional agents. Therefore, the present study aims to select safe herbal extracts with potent antibacterial properties as dietary supplementation for juvenile red hybrid tilapia (Oreochromis sp.). Five Malaysian local herbal extracts of methanol and aqueous i.e. Cosmos caudatus (ulam Raja), Curcuma mangga (temumangga), Justicia gendarussa (gandarusa), Piper betle (sireh), and Zingiber zerumbet (lempoyang) were screened for antibacterial activities against nine common fish pathogenic bacteria using agar-well diffusion method. The assay showed methanolic extracts could inhibit all of bacteria tested namely Bacillus sp., Enterococcus feacalis, Staphylococcus aureus, Streptococcus agalactiae, Aeromonas hydrophila, Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, and Vibrio alginolyticus with higher inhibitions compared to aqueous extracts. The aqueous extracts showed inhibition only towards S. aureus, S. agalactiae, A. hydrophila, and V. alginolyticus. Due to low antibacterial activities, aqueous extracts were omitted for further evaluation, which included the methanolic extracts of C. mangga and J. gendarussa. Comparative inhibitory activities between selected methanolic extracts of herbs and standard antibiotics revealed the ability of the herbs as potent antibacterial agent are presented in the following descending order of effectiveness: enrofloxacin, P. betle, oxytetracycline, Z. zerumbet, tetracycline, C. caudatus, and erythromycin. Methanolic extracts of P. betle, Z. zerumbet, and C. caudatus were investigated for in vivo toxicity. The median lethal doses (LD50) of the extracts administered intraperitoneally to Oreochromis sp. juveniles were determined to be 310.97 mg/mL (P. betle), 227.53 mg/mL (Z. zerumbet), and 234.42 mg/mL (C. caudatus). Although all of herbal extracts yielded low mortality, organ histology revealed moderate pathological changes induced by C. caudatus and Z. zerumbet that increased proportionally with the dose given. Consequently, C. caudatus and Z. zerumbet were discarded for next assessment due to their toxicity effects. Qualitative phytochemical screening was carried out for P. betle methanolic extract (PBME) prior to the identification and quantification of its major antibacterial active compounds. The phytochemical analysis showed the presence of alkaloids, phenols, flavonoids, tannins, saponins, glycosides, terpenoids, and steroids. The TLC-agar-overlay bioautography assay identified two major compounds i.e. hydroxychavicol and eugenol as the responsible compounds for antibacterial activities. The content of hydroxychavicol and eugenol in PBME were found to be 374.72±2.79 mg/g and 49.67±0.16 mg/g as quantitatively analysed by HPLC. Feeding trial was done in order to determine the effects of PBME on growth performance, blood parameters, and histology of organs of Oreochromis sp. PBME was supplemented in the diet at 0.20 g/kg (T1), 0.78 g/kg (T2), and 3.13 g/kg (T3) containing 37.47% and 4.97% of hydroxychavicol and eugenol, and fed to Oreochromis sp. for 12 weeks. The fish fed with 0.20 g/kg PBME had the best performance, and showed significant improvement in weight gain (616.23%), body length gain (6.87 cm), specific growth rate (2.34%/day), protein efficiency ratio (1.97), and feed conversion ratio (1.48). Haematological analysis showed higher trend in RBC, Hb, and Hct values, with lower WBC value in PBME-fed fish compared to control. Total serum protein, albumin, and globulin contents were improved particularly with the supplementation of PBME at 0.78 g/kg. Histological findings also revealed no adverse effects of the PBME supplementations on fish spleen and intestine. The effects of dietary supplementation of PBME in Oreochromis sp. were then assessed on survival and resistance to S. agalactiae. In 14 days of S. agalactiae post-challenge, survival and RPS of Oreochromis sp. fed with PBME was higher than untreated-control group, but not significantly different compared to OTC-treated group. The results showed PBME-treated fish had a high resistance to disease, and the efficacy of PBME as prophylaxis was equivalent to OTC antibiotic. The supplementation of PBME at 0.78 g/kg gave the best result, and it could restore the altered haematological parameters and serum protein contents in infected fish to near normal values. Histological analysis showed the degrees of damage were lesser in infected organs of PBME-treated fish compared to untreated-control fish. The results revealed the potential of PBME to ameliorate the organ damages induced by S. agalactiae. In conclusion, the current study suggests that Piper betle methanolic extract is effective as a growth and health promoter in Oreochromis sp.